2014
DOI: 10.1111/1471-0528.12571
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the second stage of labour to pelvic floor dysfunction: a prospective cohort comparison of nulliparous women

Abstract: Objective Maternal expulsive efforts are thought to damage the pelvic floor. We aimed to compare pelvic floor function and anatomy between women who delivered vaginally (VB) versus cesarean (CD) without entering the second stage of labor. Design Prospective cohort Setting University Hospital Midwifery practice Population Nulliparas Methods Pregnant nulliparas were recruited during pregnancy and women who underwent CD prior to the 2nd stage of labor at birth were recruited immediately postpartum. Both g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(70 citation statements)
references
References 31 publications
5
59
0
6
Order By: Relevance
“…As reported previously, 10,14 there was a low rate of vacuum deliveries (25 women, 6%), forceps delivery (one woman, 0.2%), episiotomy (8 women, 2%), and third or fourth degree lacerations (22 women, 5%) among the women who had a VB, and only 24 women entered the second stage of labor before delivering by a CD. There were 433 women (62%) who presented for US imaging 6 months postpartum, with 423 (299 VB and 124 CD) having full imaging of the sphincters.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…As reported previously, 10,14 there was a low rate of vacuum deliveries (25 women, 6%), forceps delivery (one woman, 0.2%), episiotomy (8 women, 2%), and third or fourth degree lacerations (22 women, 5%) among the women who had a VB, and only 24 women entered the second stage of labor before delivering by a CD. There were 433 women (62%) who presented for US imaging 6 months postpartum, with 423 (299 VB and 124 CD) having full imaging of the sphincters.…”
Section: Resultssupporting
confidence: 71%
“…Methods of the parent study and ultrasound findings have been reported in prior publications. 10,14 One expert sonologist (RH), three female pelvic medicine fellows, and one female pelvic medicine attending (RG) performed and interpreted all the imaging, with previous a publication reporting on the inter-rater reliability of this group. 9 Patients underwent both translabial (TL-US) and endoanal ultrasound (EA-US) at the same time point as part of the parent study, with comparison between these imaging modalities published previously, 15 but this manuscript concerns itself with the TL-US imaging.…”
Section: Methodsmentioning
confidence: 99%
“…Review of the available evidence allows the assumption that prolonged second-stage labor and vaginal delivery can both damage the pelvic floor [24,25]. One study shows that nearly one-third of women have levator ani denervation after their first delivery, although many recover by 6 months postpartum [26].…”
Section: Discussionmentioning
confidence: 99%
“…13,17,18 Labor and maternal characteristics were gathered at birth and included detailed examination of all lacerations to the genital tract sustained during delivery. Women with a second degree or more severe perineal laceration were evaluated by a second examiner to ensure that lacerations were graded appropriately.…”
Section: Methodsmentioning
confidence: 99%